Prion protein E219K polymorphism: from the discovery of the KANNO blood group to interventions for human prion disease - Wang, Si-Si; Meng, Zhao-Li; Zhang, Yi-Wen; Yan, Yi-Shuang; Li, Ling-Bo (Frontiers in Neurology, 2024)
KANNO is a new human blood group that was recently discovered. The KANNO antigen shares the PRNP gene with the prion protein and the prion protein E219K polymorphism determines the presence or absence of the KANNO antigen and the development of anti-KANNO alloantibodies. These alloantibodies specifically react with prion proteins, which serve as substrates for conversion into pathological isoforms in some prion diseases and may serve as effective targets for resisting prion infection. These findings establish a potential link between the KANNO blood group and human prion disease via the prion protein E219K polymorphism. We reviewed the interesting correlation between the human PRNP gene’s E219K polymorphism and the prion proteins it expresses, as well as human red blood cell antigens. Based on the immune serological principles of human blood cells, the prion protein E219K polymorphism may serve as a foundation for earlier molecular diagnosis and future drug development for prion diseases.